Extending the Reach of Research: Introducing Open Accessible Summaries at Language Learning. Issue 1 (27th January 2019) - Marsden, Emma; Trofimovich, Pavel; Ellis, Nick
Abstract: Open science practices, which include efforts to enhance accessibility to data and materials and to improve the dissemination of findings to broader audiences, have been at the forefront of the open science movement worldwide. Language Learning is proud to extend its support of open science practices by participating in the OASIS (Open Accessible Summaries in Language Studies) initiative, which aims to make language‐related research openly available and easily accessible, both physically and conceptually. As part of the OASIS initiative, Language Learning now publishes accessible summaries of all accepted articles, including reviews and syntheses. Written in nontechnical language, accessible summaries provide information about each study's goals, its design and approach, and its results, highlighting findings that may be of interest to those outside academia, such as language educators. We outline key rationales leading to the development of accessible summaries, describe their core features, and discuss some of their strengths and weaknesses.